2008
DOI: 10.1128/jb.01386-07
|View full text |Cite
|
Sign up to set email alerts
|

One Pathway Can Incorporate either Adenine or Dimethylbenzimidazole as an α-Axial Ligand of B 12 Cofactors in Salmonella enterica

Abstract: Coenzyme B 12 (Ado-Cbl) and vitamin B 12 (CN-B 12 ) (Fig. 1) include the base 5,6-dimethylbenzimidazole (DMB) as an ␣-axial ligand. Prokaryotes, the only producers of vitamin B 12 , make "complete" corrinoid cofactors with a variety of alternative ␣-axial ligands, including benzimidazoles, phenols, and purines (16, 52). These alternative corrinoids may be functional equivalents of coenzyme B 12 for many bacterial enzymes, but functional differences are suggested by the selectivity of the human assimilatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
76
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 55 publications
7
76
0
Order By: Relevance
“…1C), resulting in a functional AdoCbl analog. Previous studies in Salmonella enterica, for example, found point mutations causing incorporation of adenine in place of dimethylbenzimidazole, resulting in formation of pseudo-B 12 (58). An alternative explanation is that the spontaneous mutation in some way causes increased anaerobiosis or increased resistance of NrdD to O 2 .…”
Section: Complementation Of Mutant Growth In Brothmentioning
confidence: 97%
“…1C), resulting in a functional AdoCbl analog. Previous studies in Salmonella enterica, for example, found point mutations causing incorporation of adenine in place of dimethylbenzimidazole, resulting in formation of pseudo-B 12 (58). An alternative explanation is that the spontaneous mutation in some way causes increased anaerobiosis or increased resistance of NrdD to O 2 .…”
Section: Complementation Of Mutant Growth In Brothmentioning
confidence: 97%
“…Unexpectedly, rather than uncovering genes involved in synthesizing DMB, the authors identified 25 point mutations that increase the cellular concentration of free adenine, a precursor of pseudo-B 12 (1). Thus, all of the characterized mutants pro-duced an elevated level of pseudo-B 12 that supported growth on ethanolamine.…”
mentioning
confidence: 99%
“…Another important difference between this and other studies was that growth was monitored on ethanolamine rather than methionine or propanediol. This alteration was critical because (i) the requirement for B 12 during growth on ethanolamine is more stringent than on methionine, and (ii) exogenous DMB is required for growth on ethanolamine but not on propanediol (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodobacters have the O 2 -dependent corrin ring and DMB pathways (11), whereas Thaumarchaeota likely possess the O 2 -independent pathway for the corrin ring and the O 2 -dependent DMB pathway (10). In some bacteria, pseudocobalamin can be produced if DMB synthesis is impaired; this is due to the natural presence of adenine in cells and enzyme substrate promiscuity that allows adenine to substitute for DMB in some organisms' CobT (22)(23)(24)(25)(26)(27). Cyanobacteria use the O 2 -independent pathway for corrin ring synthesis and neither pathway for DMB synthesis (11,18) (Fig.…”
mentioning
confidence: 99%